2022
DOI: 10.3389/fphar.2022.890202
|View full text |Cite
|
Sign up to set email alerts
|

Neohesperidin Protects Angiotensin II-Induced Hypertension and Vascular Remodeling

Abstract: Vascular remodeling due to hypertension is one of the major health challenges facing countries around the world. Neohesperidin, a flavonoid glycoside found in citrus fruits, is an antioxidant. Neohesperidin has been studied for a variety of diseases in addition to hypertension. In this study, angiotensin II was used to induce hypertension in mice (490 ng/kg/min, 14 days). We used H&E, Masson, immunofluorescence, dihydroethidine and qPCR to evaluate the effect of Nehesperidin (50 mg/kg/day, 16 days) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Accumulation of catalases attenuates the progression of vascular remodeling and hypertension by reducing oxidative stress. [300][301][302][303] Immunity/inflammation pathway The majority of components involved in the Immunity/inflammatory responses circulate through the blood and vasculature. And low-grade immune response plays an important role in the initiation and maintenance of elevated BP.…”
Section: Etcmentioning
confidence: 99%
“…Accumulation of catalases attenuates the progression of vascular remodeling and hypertension by reducing oxidative stress. [300][301][302][303] Immunity/inflammation pathway The majority of components involved in the Immunity/inflammatory responses circulate through the blood and vasculature. And low-grade immune response plays an important role in the initiation and maintenance of elevated BP.…”
Section: Etcmentioning
confidence: 99%
“…Jurnal Teknologi Pertanian Andalas Vol. 27, No.1, Maret 2023, ISSN 1410-1920, EISSN 2579 Agung Yogeswara ================================================================================ 14 Kelompok flavanone yang dihasilkan pada ekstrak cair kental buah mengkudu dengan metode pengeringan diangin-anginkan dan dioven adalah 5,7-Dihydroxy-6,8-dimethyl-3-(3',4'dihydroxybenzyl)chroman-4-one yang memiliki potensi sebagai anti-mutagenik dan bermanfaat dalam pencegahan kanker (Lin et al, 2014) dan neohesperidin yang berfungsi sebagai antihipertensi yang menghambat angiotensin II agar tidak terjadinya kerusakan Reactive Oxygen Species (ROS) dan deoxyribonuleic acid (DNA) pada sel endotel vena umbilikalis manusia (Zhang et al, 2022). KESIMPULAN 1.…”
Section: B Kandungan Komponen Profil Senyawa Flavonoid Ekstrak Buah M...unclassified
“…10 Recent reports have demonstrated that increases in AngII levels, particularly through the AngII type 1 receptor (AT-1R), induce tissue brosis in the heart, kidneys, liver, and vessels. [11][12][13][14][15] AngII receptors are expressed in the retina and sclera, and increased expression of AngII activates retinal cells and scleral broblasts. 16,17 One study showed that selectively inhibiting AT-1R with losartan decreases activation of the scleral broblasts after ocular hypertension and protects the RGCs.…”
Section: Introductionmentioning
confidence: 99%